2016
DOI: 10.1097/mpg.0000000000001141
|View full text |Cite
|
Sign up to set email alerts
|

Tacrolimus Predose Concentration Is Associated With Hypertension in Pediatric Liver Transplant Recipients

Abstract: Given the high prevalence of masked hypertension, ABPM should be performed in all pediatric LT recipients. Systolic and diastolic hypertension is associated with TAC C0; therefore, children with a higher target TAC C0 require a more intensive blood pressure surveillance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(44 citation statements)
references
References 42 publications
1
43
0
Order By: Relevance
“…Both might indicate a potential influence of immunosuppressive therapy. Trough levels, particularly of tacrolimus, with similar ranges to those in our cohort have been shown to be associated with both systolic and diastolic hypertension in pediatric LT recipients …”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Both might indicate a potential influence of immunosuppressive therapy. Trough levels, particularly of tacrolimus, with similar ranges to those in our cohort have been shown to be associated with both systolic and diastolic hypertension in pediatric LT recipients …”
Section: Discussionsupporting
confidence: 78%
“…Trough levels, particularly of tacrolimus, with similar ranges to those in our cohort have been shown to be associated with both systolic and diastolic hypertension in pediatric LT recipients. (39) Elevated IMT, compatible with nascent atherosclerosis, was present in 57% of children in our cohort. This frequency is in line with the recently published study by Perito et al (17) No exact prevalence of pathological IMT is reported in this study.…”
Section: Discussionmentioning
confidence: 59%
“…In those patients requiring treatment for hypertension, a potential screening strategy for secondary end organ damage includes 6-monthly testing for proteinuria, annual fundoscopy and annual cardiac sonography. 6,10,22,23,31,33,42,45,48 These investigations enable the detection of hypertensive end organ damage in an early subclinical phase and they can be considered as an intermediate endpoint for monitoring treatment. 48 Whether it is cost-effective to perform them in all patients with hypertension-even if well-controlled-remains to be determined by future research.…”
Section: Monitoringmentioning
confidence: 99%
“…Whereas renal issues observed within 1-2 years from LTx were often related to acute injuries, the physiopathology of renal damage observed in the late "crucial pe- Moreover, HTN has been associated with tacrolimus predose concentration, with the need of amore intensive blood pressure surveillance in patients with high tacrolimus target to achieve. 106 Given the high prevalence of masked hypertension, it is recommended to perform the ambulatory blood pressure measurement on all liver transplanted children, not to under-diagnose HTN. 107 However, referrals to a pediatric nephrologist should be early made for patients with repeated blood pressures > 95th percentile, especially if associated with microalbumin/creatinine ratio > 32.5 mg/g.…”
Section: Chroni C K Idne Y D Is E a S E Af Ter Ped Iatri C Liver Trmentioning
confidence: 99%
“…Moreover, HTN has been associated with tacrolimus pre‐dose concentration, with the need of amore intensive blood pressure surveillance in patients with high tacrolimus target to achieve 106 …”
Section: Chronic Kidney Disease After Pediatric Liver Transplantmentioning
confidence: 99%